PERANCANGAN PROSEDUR PENERIMAAN KAS DALAM MENINGKATKAN PENGENDALIAN INTEREN PADA BENGKEL MOTOR APFAH - Ryan Al Rachmat (Universitas Tridinanti, 2021)
The purpose of this study was to determine the cash receipts procedures in the increase of internal controls on a motorcycle Workshop Apfah. The method of analysis used in the conduct of research is by using the method of Qualitative Descriptive analysis. The results of the research that has been done shows that 1. The system of cash receipts that are in a Motor Workshop Apfah not support the operation of the company. It can be seen from the absence of a separation of responsibilities between the functions related to the system of cash receipts. 2. The design of the cash receipts Bengkel Motor Apfah is based on the procedure-a procedure that has been running in the company. The design is made, among others: the design of organizational structure, design flow chart document. In the design flow chart documents the researcher changes in certain procedures in the system and do the addition of on the documents that exist in the system of cash receipts of the company.Keywords: The Design Procedure, Cash Receipts, Internal Control